Konstruksi Predominant Leader dalam Kebijakan Moon Jae In terhadap Jepang dalam isu Comfort Women pada Tahun 2017-2022 - Candelaria, Arizki Putri (Indonesian Journal of Peace and Security Studies (IJPSS), 2023)
Comfort Women refers to the practice of forced sexual services on thousands of women by Japanese soldiers during World War II. This issue has been a source of tension in relations between South Korea and Japan for several years. In this research, the concept of "predominant leader" is used as a lens for analyzing the role played by President Moon Jae-in in making various policies related to this issue. The method used is descriptive-qualitative with literature study techniques, and the data used is secondary data originating from books, journals, and official websites. This research includes an analysis of several of Moon Jae In's foreign policies towards Japan, such as efforts to register the history of comfort women at UNESCO, demands for compensation against Japanese companies, withdrawal from GSOMIA, and the dissolution of the Reconciliation and Healing Foundation. The results of this research illustrate the complexity of the comfort women issue, with emphasis on ‘goal-driven’ and ‘situationally responsive’ aspects when it comes to policies issued in his effort to seek justice for the victims